„Auch wir sind das Volk“1. Zu Einwanderung und Ankommen in essayistischen Texten der jungen postmigrantischen Generation in Deutschland - Rutka, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The paper provides an analysis of three essayistic works of the young post-immigrant generation representatives: Lena Gorelik, Jagoda Marinić and Maxi Obexer. The significant affinity of the essayistic texts consists in the intercultural and self-reflexive perspective of the authors who expound issues related to traditional classifications and terms of culture alterity and diversity. The essays put issues of the language, designation and acceptance within the context of the current migration movements in the focus of attention. For the three authors who are established in the interculturality it is of great importance to present and reflect upon the contingency of discourses which are attributed to the essentialism culture concepts, and also to question and update the inherited terminology of the current integration discourse.

Artykuł zawiera analizę trzech eseistycznych prac przedstawicielek młodego pokolenia postimigrantów: Leny Gorelik, Jagody Marinić i Maxi Obexer. Istotne powinowactwo tych tekstów polega na międzykulturowej i autorefleksyjnej perspektywie autorek, które rozważają kwestie związane z tradycyjnymi klasyfikacjami i pojęciami różnorodności kulturowej. W esejach tych w centrum uwagi znajdują się kwestie języka, określania i akceptacji w kontekście obecnych ruchów migracyjnych. Dla autorek wyrosłych w świecie interkulturowości bardzo ważne jest opisanie i refleksja nad kontyngentyzmem dyskursów esencjalistycznych, a także kwestionowanie i aktualizacja odziedziczonej terminologii obecnego dyskursu integracyjnego.
“We are the people as well”. Immigration and Arrival in Essayistic Works of Young Post-immigrant Generation in Germany
„My także jesteśmy narodem”. Problem imigracji i osiedlenia w eseistyce młodego postmigracyjnego pokolenia w Niemczech
Keywords: essayistic works; young post-immigrant generation in Germany; immigration; integration; teksty eseistyczne; młode pokolenie postmigracyjne w Niemczech; emigracja; integracja